DESIGN OF HEAD TRUCK DISPATCHING STRATEGY IN CONTAINER TERMINAL USING DISCRETE EVENT SIMULATION - Zikra, Amalia
In attempt to improve container terminal time efficiency, transfer vehicle dispatching strategy is applied as an algorithm to determined which container to prioritize if more than one quay cranes or yard cranes are calling (are needing) the transfer vehicle. Transfer vehicle dispatching strategy synchronize the equipment involved in container transfer operation from quay to yard, as in quay crane, transfer vehicle, and yard crane, to achieve a low terminal waterside service time. To find the best transfer vehicle dispatching strategy for Lamong Bay Port, discrete event simulations were carried out for each approach to be compared, namely the dedicated to STS crane approach, the due-time-based approach, and the inventorybased approach. The simulation is executed using the Plant Simulation software. Resulting performance is the terminal waterside service time which, when sorted from best to worst, is 1.136 minutes/TEU for the inventory-based approach, 1.144 minutes/TEU for the dedicated to STS crane approach, and 1.427 minutes/TEU for the due-timebased approach. Thus, the chosen transfer vehicle dispatching strategy for Lamong Bay Port is transfer vehicle dispatching strategy using inventory-based approach with the advantage of being the lowest terminal seaside service time compared to other approaches. The drawback of this approach is that it has the highest head truck waiting time in quay buffer area and requires computer to run the assignment algorithm and record real time status and position of each transfer vehicle.